Proceedings of the Ocean Drilling Program, 146 Part 1 Scientific Results 1995
DOI: 10.2973/odp.proc.sr.146-1.215.1995
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures in Accreted Sediments of the Cascadia Margin

Abstract: Deformed sediments collected from drilling at the Cascadia forearc were examined using optical and electron microscopy. A wide range of microstructures was encountered in a sample suite consisting mainly of fine-grained sediments. Most of the samples were recovered from the Oregon sector of the accretionary wedge, at Site 891, located at the deformation front, and Site 892, located on the second thrust ridge. For purposes of comparison, we also examined a small number of samples from the undeformed Cascadia Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Grain size analyses of material from Site 889 suggested 50–60% clay fraction in the top 50 m, increasing to 70–75% at 130 m depth and falling again to ∼50% close to the BSR [ Camerlenghi et al , 1995]. However, a high proportion of the clay size fraction appears to consist of angular rock and mineral fragments rather than clay minerals [ Clennell and Maltman , 1995]. On the basis of XRD and XRF analyses, Kopf et al [1995] suggest that clay minerals do not exceed 35% by volume, with 15–20% quartz and the remaining fraction consisting of mainly plagioclase feldspar with minor mica and calcite.…”
Section: Resultsmentioning
confidence: 99%
“…Grain size analyses of material from Site 889 suggested 50–60% clay fraction in the top 50 m, increasing to 70–75% at 130 m depth and falling again to ∼50% close to the BSR [ Camerlenghi et al , 1995]. However, a high proportion of the clay size fraction appears to consist of angular rock and mineral fragments rather than clay minerals [ Clennell and Maltman , 1995]. On the basis of XRD and XRF analyses, Kopf et al [1995] suggest that clay minerals do not exceed 35% by volume, with 15–20% quartz and the remaining fraction consisting of mainly plagioclase feldspar with minor mica and calcite.…”
Section: Resultsmentioning
confidence: 99%
“…48, this volume). Study of cores from the Cascadia margin has revealed similar structures including anastomosing veins, shear bands, incipient scaly fabrics and blocky mosaic structures that allow fluid flow when held open by high pore pressures (Clennell and Maltman, 1995). Anastomosing scaly clay was also observed in the toe region off Barbados (Prior and Behrmann, 1990).…”
Section: Evidence Of Overpressuring At Depthmentioning
confidence: 99%
“…Scaly foliation has also become a typical fabric nomenclature in sheared mudstones drilled in submarine subduction complex Maltman and Vannucchi 2004). Barbados (Cowan et al 1984;Labaume et al 1997;Takizawa and Ogawa 1999), Nankai (Taira et al 1992;Maltman et al 1993), Costa Rica (Vannucchi and Tobin 2000), and Cascadia (Clennell and Maltman 1995) all contain subduction complexes where scaly fabric is commonly associated with shearing. Scaly fabric has been also described in cores of basalts and boninites from the Mariana Trough (Hussong and Uyeda 1981) and from serpentinites in Guatemala (von Huene et al 1985).…”
Section: From Scaly Clays To Scaly Cleavagementioning
confidence: 99%